Radiological Perspective of Covid-19 Pneumonia in Tertiary Care Hospital, Karachi (Medical Forum Monthly, 2022)
Objective: To evaluate the radiographic patterns in COVID associated pneumonia in a tertiary care hospital of Karachi.Study Design: Analytic studyPlace and Duration of Study: This study was conducted in specifically designed COVID wards and HDU in Dow University Hospital, Karachi between 1st June 2020 to 15th July 2020, by reviewing the admission records of COVID diagnosed patients.Materials and Methods: A total of 150 patients presented with pulmonary symptoms were evaluated for chest radiographs.Results: Out of 150 COVID detected patients, 80 were males (53.33%) and 70(46.66%) were females with a mean age of 51.14±15.96 years. Frequent radiographic patterns were diffuse infiltrates occupying more than half lung field 56(37.33%), diffuse infiltrates less than half of lung field 45 patients (30%), lobar pneumonia in 9(6%) and cardiomegaly with basal infiltrates were observed in 7 patients (4.6%). Dominant symptoms were shortness of breath on exertion 105 patients (70%), fever 60(40%). The most common signs observed were hyperventilation 105(70%) and crepitation’s 30(20%). The most common comorbidities observed in the study were Uncontrolled Diabetes 114(74%), Hypertension 76(50.6%), and ischemic heart disease 52(34.66%).Conclusion: The majority of COVID detected with pneumonia were male, common radiographic patterns were pulmonary infiltrates. Lobar pneumonia and pleural effusion were rare findings and typically seen in severe disease where patients need mechanical ventilation.